1999
DOI: 10.1046/j.1525-1446.1999.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Building Community Health Nursing in the People's Republic of China: A Partnership Between Schools of Nursing in Ottawa, Canada, and Tianjin, China

Abstract: Community health nursing in China is an emerging specialty. A multi-component collaborative endeavor between the Schools of Nursing of Tianjin Medical University, China, and the University of Ottawa, Canada is described. This project, funded by the Canadian International Development Agency, commenced in 1989. It has laid the groundwork for an expanded role for community health nurses in Tianjin, a municipality of 11 million people located in Northeast China. The historical context for the evolution of communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…the multicomponent collaborative endeavour between the Tianjing Medical University and the University of Ottawa Schools of Nursing to build community‐based programmes ( Edwards et al 1999; Papai et al 1999), and…”
Section: Recent Reforms and Developments In Nursing Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…the multicomponent collaborative endeavour between the Tianjing Medical University and the University of Ottawa Schools of Nursing to build community‐based programmes ( Edwards et al 1999; Papai et al 1999), and…”
Section: Recent Reforms and Developments In Nursing Educationmentioning
confidence: 99%
“…Exchange programmes between sister schools, such as Hunan Medical University and Yale University, generated enthusiasm and positive outcomes (Watkins 1996). Perhaps the two exemplary projects in this regard are: • the multicomponent collaborative endeavour between the Tianjing Medical University and the University of Ottawa Schools of Nursing to build community-based programmes (Edwards et al 1999;Papai et al 1999), and • the Community-Based International Learning Programmes -China Project between Schools of Nursing, Beijing Medical University and the University of Michigan (University of Michigan School of Nursing 1999).…”
Section: Internationalization Of Nursing Educationmentioning
confidence: 99%
“…Despite recognition of the usefulness of international faculty‐exchange programmes in nursing, there is minimal literature on the topic. Based on a Cumulative Index to Nursing and Allied Health Literature (CINAHL) review over the last 5 years, there were only four reports focusing on international nursing faculty exchanges (Thomas et al 1994; Byrne & Falk 1996; Byrne 1998; Edwards et al 1999). Byrne (1998) reported informatively on her 6‐week faculty exchange experience at a Swedish university, in which her activities included teaching, consultation and socialization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this was a project carried out specifically to prepare the Jordan faculty in nursing education and the visitors were not integrated as members of the faculty. Finally, Edwards et al (1999) gave an account of their partnership between the school of nursing in Ottawa and Tianjin, China, in which nurses from the Canadian university taught an elective course to nursing students in China. They found that it was important to understand the culture‐specific features of the change process in the new setting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tlou (1998) described developing an international nursing education partnership as a series of multiple processes rather than procedural tasks, and recommended that the process of initiating a partnership begin with learning about partners' institutional and human resources. Other authors indicated the need to learn about the contexts for health care and education (Byrne, 1998;Carty & White, 1996;Edwards, Bunn, Mei, & Hui, 1999;Johnson, Ghebreyohanes, Cunningham, Kutenplon, & Bouey, 2007), existing resources (Byrne, 1998;Johnson et al, 2007), learner characteristics (Byrne, 1998;Johnson et al, 2007), curriculum needs (Bryne, 1998;Johnson et al, 2007), nursing roles and scopes of practice (Kuehn et al, 2005), and sociopolitical influences on the health care environment (Girot & Enders, 2004).…”
Section: Learning Needsmentioning
confidence: 99%